High‐Quality Two‐Dimensional Metal‐Organic Framework Nanofilms for Nonvolatile Memristive Switching. Issue 4 (22nd January 2021) - Liu, Lei; Dong, Jie; Liu, Jie; Liang, Qiu; Song, Yaru; Li, Wanhui; Lei, Shengbin; Hu, Wenping
Abstract : Metal‐organic framework (MOFs) nanofilm offer new perspectives as active layers in memristor devices due to their large surface area, high chemical and thermal stability, permanent porosity, and tunable structure. Though various methods are reported for the preparation of MOF nanofilms, the development of new methods to improve the quality is still essential toward their broader and large‐scale application. Herein, Cu3 (HHTP)2 (HHTP = 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene) nanofilms with a large lateral dimension, high homogeneity, and controllable thickness (from 45 to 130 nm) are prepared at the air–liquid interface and further applied in memory devices. The device exhibits a forming‐free, superior retention (1.2 × 10 4  s) performance with low power consumption and reliability. Kelvin probe force microscopy (KPFM) is applied to gain an insight into the switching mechanism. Herein, a facile and effective method for the preparation of MOF nanofilms is provided and the potential application of MOFs in electronic devices is further proved. Abstract : High‐quality Cu3 (HHTP)2 nanofilms with a large area and controllable thickness are prepared by the facile air–water interface method. The nanofilms are further used as an active layer in Au/Cu3 (HHTP)2 nanofilms/ITO memory devices and the as‐fabricated devices exhibit superior reliability and excellent stability.